2022
DOI: 10.22201/ia.01851101p.2022.58.02.19
|View full text |Cite
|
Sign up to set email alerts
|

Observational Constraints on the Hd 5980 Wind-Wind Collision

Abstract: Analysis of spectral line profile variations observed over 6 decades in the Wolf-Rayet system HD 5980 lead to the conclusion that Star A, the variable member of the system, has always dominated the wind collision zone (WCZ), contrary to suggestions that before 1994 the stronger wind belonged to its close companion, Star B. The observed variations are caused by a combination of physical occultations, wind eclipses and emission and absorption originating in the WCZ. The effects caused by the leading WCZ branch, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Furthermore, because the bloating induced by E  ultimately comes from the orbital energy, the orbit will shrink. As suggested by Koenigsberger & Moreno (2016), this could lead to a runaway process in which the bloating star absorbs a systematically increasing amount of orbital energy. One possible outcome is the ejection of a shell, allowing the star to contract and stabilize.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, because the bloating induced by E  ultimately comes from the orbital energy, the orbit will shrink. As suggested by Koenigsberger & Moreno (2016), this could lead to a runaway process in which the bloating star absorbs a systematically increasing amount of orbital energy. One possible outcome is the ejection of a shell, allowing the star to contract and stabilize.…”
Section: Discussionmentioning
confidence: 95%
“…However, additional binary interaction effects exist that can affect a star's internal structure and thus its HRD location. Koenigsberger & Moreno (2016) suggested that if tidal shear energy dissipation in an asynchronously rotating binary star is fed into the internal layers as heat, this would cause the star to increase its radius. Estrella-Trujillo et al (2023) demonstrated that if the tidal heating is injected into a stellar model, the reaction of the star is indeed to increase its radius, but, in addition, it becomes hotter and more luminous than the corresponding standard model, and its evolutionary path crosses the HRD regions occupied by BSSs.…”
Section: Introductionmentioning
confidence: 99%
“…Several Magellanic Cloud systems are host to multiple WN+WN stars, including BAT99-116 (Mk 34, Tehrani et al 2019), andBAT99-118 (R144, Shenar et al 2021), so we adopt equal line contributions from each component since mass ratios are close to unity, which should be a reasonable assumption with the potential exception of AB5 (HD 5980, Koenigsberger et al 2014). Since AB5 is known to be spectroscopically variable (Koenigsberger et al 2022), we have selected the HST/STIS dataset from 2016 (phase 0.36) instead of 2014 (phase 0.0) (Hillier et al 2019). R140a is omitted since it involves a mix of WN and WC populations which are difficult to deblend (Castro et al 2018).…”
Section: Magellanic Cloud Wr Starsmentioning
confidence: 99%
“…LMC weak-lined WN6-8 stars extend the Galactic sequence to higher luminosities, including R144 (BAT99-118), which is host to a multiple WN+WN system (Shenar et al 2021) and R145 (BAT99-119) which is also a binary system (Shenar et al 2019). There are too few SMC late-type WN stars to draw robust conclusions, although the high luminosity SMC system AB 5 (HD 5980) is also multiple (Koenigsberger et al 2014(Koenigsberger et al , 2022 Tables 2-3 provide calibrations of He 𝜆4686 line luminosities for WN2-8 (N=140), WN9-11 (N=12), Of/WN (N=8) and WN/C (N=9) stars, respectively, together with other prominent optical emission lines. This highlights features that may be detectable in high S/N observations of WR galaxies, notably the 𝜆4100 complex in WN stars which is largely unaffected by nebular emission, in contrast with H𝛼, H𝛽, He 𝜆5876.…”
Section: Wn Of/wn and Wn/c Starsmentioning
confidence: 99%
“…A single mechanism may be operating over a wide range of energy and mass, different mechanisms may produce the same observables, or several mechanisms may cooperate. Rotation (Langer 1998;Zhao & Fuller 2020;Shi & Fuller 2022), binary interaction (Kenyon & Gallagher 1985;Gallagher 1989;Smith 2011;Owocki et al 2019;Quataert et al 2016;Soker 2001Soker , 2004Soker , 2007Kashi & Soker 2009;Smith et al 2003;Koenigsberger 2004), and stellar mergers (Iben 1999;Portegies Zwart & van den Heuvel 2016;Hirai et al 2021) may also play a crucial role in shaping the LBV phenomenon.…”
Section: Classical and Giant Eruption Lbvsmentioning
confidence: 99%